Comparative Study of Selected Excipients' Influence on Carvedilol Release from Hypromellose Matrix Tablets - Tadej Ojsteršek; Grega Hudovornik; Franc Vrečer (MDPI AG, 2023)
Solid dosage forms based on hypromellose (HPMC) with prolonged/extended drug release are very important from the research and industrial viewpoint. In the present research, the influence of selected excipients on carvedilol release performance from HPMC-based matrix tablets was studied. A comprehensive group of selected excipients was used within the same experimental setup, including different grades of excipients. Compression mixtures were directly compressed using constant compression speed and main compression force. LOESS modelling was used for a detailed comparison of carvedilol release profiles via estimating burst release, lag time, and times at which a certain % of carvedilol was released from the tablets. The overall similarity between obtained carvedilol release profiles was estimated using the bootstrapped similarity factor (f2). In the group of water-soluble carvedilol release modifying excipients, which produced relatively fast carvedilol release profiles, POLYOXᵀᴹ WSR N-80 and Polyglykol® 8000 P demonstrated the best carvedilol release control, and in the group of water-insoluble carvedilol release modifying excipients, which produced relatively slow carvedilol release profiles, AVICEL® PH-102 and AVICEL® PH-200 performed best.